Employing of CRISPR-Cas System as an Antimicrobial Agent (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
Background:Improper use of antibiotics and an incomplete administration of the drug may assist to the emergence of antibiotic-resistant bacteria. Using the CRISPR-Cas9 system acts as a precision biological tool to remove resistance genes from the bacterial genome, thereby reducing the appearance of resistant bacterial strains. CRISPR and Cas9 genes work as an adaptive immune systems in widespread bacteria and Achaea. The fragments of invading DNA were integrated into the host genome at the CRISPR locus, where they serve as transcription templates for the synthesis of RNA that aim Cas nucleases to cut foreign nucleic acids. The Cas enzyme identifies target sites in chromosomal sequences, leading to destroy foreign DNA.  In our review, we discuss the mechanism of DNA destruction achieved by CRISPR-Cas systems applied as a powerful technology to eliminate plasmids or destroy bacterial cell.